Carotenoids and amphibians: effects on life history and susceptibility to the infectious pathogen, Batrachochytrium dendrobatidis. (13th March 2015) - Cothran, Rickey D.; Gervasi, Stephanie S.; Murray, Cindy; French, Beverly J.; Bradley, Paul W.; Urbina, Jenny; Blaustein, Andrew R.; Relyea, Rick A.
Abstract : Carotenoids are components of an animal's diet that are considered beneficial because they typically provide increased immune capacity. However, little research has been done in amphibians. We found that carotenoids can cause lower survival, slower development and growth in amphibians, and no mitigating effects against a common amphibian disease. Abstract : Carotenoids are considered beneficial nutrients because they provide increased immune capacity. Although carotenoid research has been conducted in many vertebrates, little research has been done in amphibians, a group that is experiencing global population declines from numerous causes, including disease. We raised two amphibian species through metamorphosis on three carotenoid diets to quantify the effects on life-history traits and post-metamorphic susceptibility to a fungal pathogen ( Batrachochytrium dendrobatidis ; Bd ). Increased carotenoids had no effect on survival to metamorphosis in gray treefrogs ( Hyla versicolor ) but caused lower survival to metamorphosis in wood frogs [ Lithobates sylvaticus ( Rana sylvatica )]. Increased carotenoids caused both species to experience slower development and growth. When exposed to Bd after metamorphosis, wood frogs experienced high mortality, and the carotenoid diets had no mitigating effects. Gray treefrogs were less susceptible to Bd, which prevented an assessment of whether carotenoids could mitigate the effects of Bd . Moreover, carotenoids had no effect on pathogen load. As one of only a few studies examining the effects of carotenoids on amphibians and the first to examine potential interactions with Bd, our results suggest that carotenoids do not always serve amphibians in the many positive ways that have become the paradigm in other vertebrates.